Agricultural pesticide use and adenocarcinomas of the stomach and oesophagus. Issue 9 (18th August 2004) - Lee, W J; Lijinsky, W; Heineman, E F; Markin, R S; Weisenburger, D D; Ward, M H
Abstract : Aims: To evaluate the risk of the stomach and oesophageal adenocarcinomas associated with farming and agricultural pesticide use. Methods: Population based case-control study in eastern Nebraska. Telephone interviews were conducted with men and women diagnosed with adenocarcinoma of the stomach (n = 170) or oesophagus (n = 137) between 1988 and 1993, and controls (n = 502) randomly selected from the same geographical area. Unconditional logistic regression was used to calculate adjusted odds ratios (ORs) for farming and for use of individual and chemical classes of insecticides and herbicides, including pesticides classified as nitrosatable (able to form N-nitroso compounds on reaction with nitrite). Non-farmers were used as the reference category for all analyses. Results: Ever living or working on a farm, duration of farming, and size of the farm were not associated with stomach or oesophageal adenocarcinomas. There was no association for either cancer with ever-use of insecticides (stomach OR 0.9, 95% CI 0.6 to 1.4; oesophagus OR 0.7, 95% CI 0.4 to 1.1) or herbicides (stomach OR 0.9, 95% CI 0.5 to 1.4; oesophagus OR 0.7, 95% CI 0.4 to 1.2). Likewise, individual pesticides, including individual nitrosatable pesticides, were not significantly associated with risk. Conclusions: No significant associations were found between specific agricultural pesticide exposures and the risk of stomach or oesophageal adenocarcinomas among Nebraska farmers.